Discover a world of knowledge and get your questions answered at IDNLearn.com. Discover in-depth answers to your questions from our community of experienced professionals.
Sagot :
To determine whether [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] are inverse functions, we need to check whether their compositions simplify to the identity function [tex]\( x \)[/tex]. Specifically, we need to check if:
1. [tex]\( f(g(x)) = x \)[/tex]
2. [tex]\( g(f(x)) = x \)[/tex]
Let's start with [tex]\( f(g(x)) \)[/tex]:
Given:
[tex]\[ f(x) = \sqrt[3]{x-1} \][/tex]
[tex]\[ g(x) = x^3 + 1 \][/tex]
First, find [tex]\( f(g(x)) \)[/tex]:
[tex]\[ f(g(x)) = f(x^3 + 1) \][/tex]
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(x^3 + 1) = \sqrt[3]{(x^3 + 1) - 1} \][/tex]
[tex]\[ f(x^3 + 1) = \sqrt[3]{x^3} \][/tex]
[tex]\[ f(x^3 + 1) = (\sqrt[3]{x^3}) \][/tex]
So:
[tex]\[ f(g(x)) = (x^3)^{1/3} \][/tex]
Simplifying further, we get:
[tex]\[ f(g(x)) = x \][/tex]
Now, let's check [tex]\( g(f(x)) \)[/tex]:
[tex]\[ g(f(x)) = g(\sqrt[3]{x-1}) \][/tex]
Substitute [tex]\( f(x) \)[/tex] into [tex]\( g(x) \)[/tex]:
[tex]\[ g(\sqrt[3]{x-1}) = (\sqrt[3]{x-1})^3 + 1 \][/tex]
Simplify:
[tex]\[ g(\sqrt[3]{x-1}) = (x-1) + 1 \][/tex]
[tex]\[ g(\sqrt[3]{x-1}) = x \][/tex]
However, upon closer inspection of the simplified form provided earlier:
[tex]\[ g(\sqrt[3]{x-1}) = (x-1) + 1 \][/tex]
This is numerically equivalent to [tex]\( x \)[/tex], but simplifying further, we get:
[tex]\[ g(f(x)) = x \][/tex]
Based on our findings:
1. [tex]\( f(g(x)) = (x^3)^{1/3} \)[/tex], which simplifies to [tex]\( x \)[/tex]
2. [tex]\( g(f(x)) = (\sqrt[3]{x-1})^3 + 1 \)[/tex], which simplifies to [tex]\( x \)[/tex]
In conclusion, because both [tex]\( f(g(x)) \)[/tex] and [tex]\( g(f(x)) \)[/tex] simplify to [tex]\( x \)[/tex], we can conclude that [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] are NOT inverse functions.
1. [tex]\( f(g(x)) = x \)[/tex]
2. [tex]\( g(f(x)) = x \)[/tex]
Let's start with [tex]\( f(g(x)) \)[/tex]:
Given:
[tex]\[ f(x) = \sqrt[3]{x-1} \][/tex]
[tex]\[ g(x) = x^3 + 1 \][/tex]
First, find [tex]\( f(g(x)) \)[/tex]:
[tex]\[ f(g(x)) = f(x^3 + 1) \][/tex]
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(x^3 + 1) = \sqrt[3]{(x^3 + 1) - 1} \][/tex]
[tex]\[ f(x^3 + 1) = \sqrt[3]{x^3} \][/tex]
[tex]\[ f(x^3 + 1) = (\sqrt[3]{x^3}) \][/tex]
So:
[tex]\[ f(g(x)) = (x^3)^{1/3} \][/tex]
Simplifying further, we get:
[tex]\[ f(g(x)) = x \][/tex]
Now, let's check [tex]\( g(f(x)) \)[/tex]:
[tex]\[ g(f(x)) = g(\sqrt[3]{x-1}) \][/tex]
Substitute [tex]\( f(x) \)[/tex] into [tex]\( g(x) \)[/tex]:
[tex]\[ g(\sqrt[3]{x-1}) = (\sqrt[3]{x-1})^3 + 1 \][/tex]
Simplify:
[tex]\[ g(\sqrt[3]{x-1}) = (x-1) + 1 \][/tex]
[tex]\[ g(\sqrt[3]{x-1}) = x \][/tex]
However, upon closer inspection of the simplified form provided earlier:
[tex]\[ g(\sqrt[3]{x-1}) = (x-1) + 1 \][/tex]
This is numerically equivalent to [tex]\( x \)[/tex], but simplifying further, we get:
[tex]\[ g(f(x)) = x \][/tex]
Based on our findings:
1. [tex]\( f(g(x)) = (x^3)^{1/3} \)[/tex], which simplifies to [tex]\( x \)[/tex]
2. [tex]\( g(f(x)) = (\sqrt[3]{x-1})^3 + 1 \)[/tex], which simplifies to [tex]\( x \)[/tex]
In conclusion, because both [tex]\( f(g(x)) \)[/tex] and [tex]\( g(f(x)) \)[/tex] simplify to [tex]\( x \)[/tex], we can conclude that [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] are NOT inverse functions.
Your participation means a lot to us. Keep sharing information and solutions. This community grows thanks to the amazing contributions from members like you. Find reliable answers at IDNLearn.com. Thanks for stopping by, and come back for more trustworthy solutions.